Thermodynamic sweet spot for high-efficiency, dilute, boosted gasoline engines. (June 2013) - Lavoie, George A; Ortiz-Soto, Elliott; Babajimopoulos, Aristotelis; Martz, Jason B; Assanis, Dennis N
Recent developments in ignition, boosting, and control systems have opened up new opportunities for highly dilute, high-pressure combustion regimes for gasoline engines. This study analytically explores the fundamental thermodynamics of operation in these regimes under realistic burn duration, heat loss, boosting, and friction constraints. The intent is to identify the benefits of this approach and the path to achieving optimum engine and vehicle-level fuel economy. A simple engine/turbocharger model in GT-Power is used to perform a parametric study exploring the conditions for best engine efficiency. These conditions are found in the mid-dilution range, a result of the tradeoff between fluid property benefits of lean mixtures and friction benefits of higher loads. Dilution with exhaust gas is nearly as effective as air dilution when compared using a 'fuel-to-charge' equivalence ratio defined as Φ′≡Φ (1-RGF) where RGF is the total residual gas fraction. Optimal brake efficiencies are obtained over a range 0.45 ≤ Φ′ ≤ 0.65 for operation up to 3 bar manifold pressure, yielding peak temperatures under 2100 K and peak pressures under 150 bar. These conditions are intermediate between homogeneous charge compression ignition and spark-ignition regimes, and are the subject of much current research on advanced combustion modes. An engine–vehicle drive train simulation shows that accessing this thermodynamic sweet spot has the potential for vehicle fuel economy gains between 23% and 58%.